PROPOSED METHOD OF DYNAMIC SPLIT DETERMINATION IN PSC BASED ON UNCERTAINTY ANALYSIS APPROACH IN DEVELOPMENT PHASE - Fikri Adriansyah, Yogie
The upstream oil and gas business basically contains high risk and uncertainty, especially during the exploration and development stages. This uncertainty is due to formation spatial heterogeneity and limited data collection to assess the recoverable reserve of a field. In addition, its development requires large costs and is also full of risk which results in an increase in investment costs than previously estimated. The highly volatile oil price is also a factor of uncertainty inherent in the upstream oil and gas business. The oil and gas cooperation contract scheme is ideally designed with the aim of providing balanced benefits between the contractor and the government. Before an oil and gas field development plan is decided to be executed, a feasibility assessment is carried out with economic indicators including internal rate of return (IRR), net present value (NPV) and pay out time (POT). However, due to high risk and uncertainty factors, in actual conditions the estimated economic value may not be achieved and result in contractor losses. For example, production estimates are smaller than expected, increased investment costs and low oil prices result in disrupted cash flow. In this study, a profit sharing calculation method will be investigated to be applied as a conventional PSC optimization to mitigate the uncertainty of field development projects. The form is a modified dynamic profit sharing scheme (sliding scale split PSC), which can improve the contractor's economy in 'low case' conditions and provide additional benefits to government revenues in 'high case' conditions automatically. In contrast to the sliding scale scheme that has been implemented, the proposed modification scheme does not use the R-factor range to determine the amount of the annual profit sharing, but uses a formula based on cumulative profitability. In the actual field case study, project revenue increased due to high oil production and prices. If the proposed dynamic split scheme is applied, this increase in revenue will provide additional benefits to the government of 21.565 MUS$ or an additional 2.83% of Government Take.